Amelioration of Muc5b mucin hypersecretion is enhanced by IL-33 after 2-APB administration in a murine model of allergic rhinitis. (May 2014) - Lin, L; Zhao, X; Yan, W; Guo, Y; Liang, S
Abstract We attempted to clarify whether hypersecretion of Muc5b mucin from mouse nasal submucosal glands that is enhanced by interleukin (IL)-33 under allergic conditions can be ameliorated by administration of 2-APB. Immunohistochemistry was used to examine both the distribution of T cells in the nasal mucosa of an allergic rhinitis mouse model and expressions of IL-33 receptor ST2 and Muc5b protein in mouse submucosal gland cells. The amounts of protein and mRNA of Orai1, Muc5b, IL-4, IL-5, IL-13 and IL-33 in mouse nasal lavage fluid (NLF) and nasal mucosa were determined using enzyme-linked immunosorbent assay and real-time reverse transcription-polymerase chain reaction. Expressions of Orai1, Muc5b, IL-4, IL-5, IL-13 and IL-33 were up-regulated in the allergic state and IL-33 increased the levels of Muc5b, IL-4, IL-5 and IL-13, but did not influence proliferation of T cells; however, ST2 was diminished in nasal submucosal gland cells. 2-APB reduced proliferation of T cells and the Orai1 level in the nasal mucosa. It also reduced the concentrations of IL-4, IL-5 and IL-13 in NLF and nasal mucosa, and hypersecretion of Muc5b from glandular cells that was enhanced by IL-33, but did not affect IL-33 production. 2-APB decreased Muc5b mucin hypersecretion from submucosal gland that was enhanced by IL-33 in allergic mice by limiting Ca2+ release-activated Ca2+ channel activity in which Orai1 plays a crucial role in the gland cells and/or by controlling channel activation in T cells and proliferation of these cells.